STRATEGI PEMERINTAH DALAM MENCEGAH ILLEGAL LOGGING DI KABUPATEN MUNA BARAT PROVINSI SULAWESI TENGGARA - Muhammad Amir; Asriani; La Ode Takdir (Halu Oleo University, 2022)
The purpose of this study is to find out and explain the strategy of the UPTD Production Forest Management Unit (KPHP) Unit VI Muna Island in tackling Illegal Logging in West Muna Regency. Using qualitative methods, this research data were obtained from interviews and documentation studies with the determination of informants by purposive sampling and analyzed using Miles and Huberman's interactive analysis methods. The results showed that the strategy of KPHP Unit VI Muna Island in tackling illegal logging activities in West Muna Regency was fairly good where in the context of protecting forest areas, a system of collaboration with the community is carried out both preventively and repressively. Then there are patrol activities in forest areas, socialization with the community in order to educate the community about forestry law, and cross-agency cooperation. To support these activities, transportation facilities are provided in the form of two-wheeled and four-wheeled vehicles. In addition, the development of human resources is also carried out through education and training.